Atomic origin of spin-valve magnetoresistance at the SrRuO3 grain boundary. Issue 4 (21st January 2020) - Li, Xujing; Yin, Li; Lai, Zhengxun; Wu, Mei; Sheng, Yu; Zhang, Lei; Sun, Yuanwei; Chen, Shulin; Li, Xiaomei; Zhang, Jingmin; Li, Yuehui; Liu, Kaihui; et al.
Abstract: Defects exist ubiquitously in crystal materials, and usually exhibit a very different nature from the bulk matrix. Hence, their presence can have significant impacts on the properties of devices. Although it is well accepted that the properties of defects are determined by their unique atomic environments, the precise knowledge of such relationships is far from clear for most oxides because of the complexity of defects and difficulties in characterization. Here, we fabricate a 36.8° SrRuO3 grain boundary of which the transport measurements show a spin-valve magnetoresistance. We identify its atomic arrangement, including oxygen, using scanning transmission electron microscopy and spectroscopy. Based on the as-obtained atomic structure, the density functional theory calculations suggest that the spin-valve magnetoresistance occurs because of dramatically reduced magnetic moments at the boundary. The ability to manipulate magnetic properties at the nanometer scale via defect control allows new strategies to design magnetic/electronic devices with low-dimensional magnetic order. Abstract : We manipulate the local magnetic properties of SrRuO3 at a grain boundary, providing new strategies to design atomic-sized magnetic/electronic devices with low-dimensional magnetic order via defect engineering.